Psychological assessment in infertility: A systematic review and meta-analysis - Tavousi, Sayed Abolfazl; Behjati, Mohaddeseh; Milajerdi, Alireza; Mohammadi, Amir Hossein (Frontiers in Psychology, 2022)
Infertility is a prevalent worldwide health issue and is defined by World Health Organization as a global health problem. Considering the importance of the psychological dimensions of infertility, various measurement tools have been used to measure the variables involved in infertility in which the most widely used are the followings: Symptom Checklist 90 (SCL90), Brief Symptom Inventory (BSI), State-Trait Anxiety Inventory Form (STAI), and Depression Anxiety Stress Scale (DASS). Therefore, given the problems of infertile people in terms of psychological dimensions, the aim of this meta-analysis was to assess the psychological assessment score in infertility. Following PRISMA protocol, we applied online database with no time restriction. Data were gathered using a random-effect model to estimate the standard mean difference (SMD) for evaluation of the strength of association analyses. Our data demonstrated a significant higher SCL90 score (CISCL90: 0.96, 0.34-1.57, heterogeneity: 94%, pheterogeneity <0.001) and a non-significant higher DASS score (CIAnxiety: 0.82, -0.14-1.79; CIDepression: 0.8, -0.28-1.87; CIStress: 0.82, -0.24-1.88). It is essential to seek for strategies to help infertile patients overcome their infertility related psychological problems.